1991
DOI: 10.1002/j.1552-4604.1991.tb03714.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hemodynamic Effects of Pinacidil in Hypertensive Patients with and without Propranolol Pretreatment

Abstract: To study the systemic and regional hemodynamic effects of the new antihypertensive agent pinacidil, the authors administered intravenously two doses of pinacidil (0.1 mg/kg) to patients with hypertension after 3 days of randomized, double-blind pretreatment with either propranolol or placebo. Pinacidil administration decreased systemic arterial pressure and total peripheral vascular resistance in both groups of patients. It also decreased pulmonary artery wedge pressure, and increased cardiac output, heart rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Due to combined cardioprotective and vasodilatory properties, K ATP channels are considered as a target for several cardiac conditions. The systemic administration of non-neuronal KCO leads to systemic vasodilation accompanied by increase in cardiac output, heart rate and circulating levels of norepinephrine and plasma renin activity (37). The present data showed that levcromakalim increased skin blood flow in humans and further support the previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Due to combined cardioprotective and vasodilatory properties, K ATP channels are considered as a target for several cardiac conditions. The systemic administration of non-neuronal KCO leads to systemic vasodilation accompanied by increase in cardiac output, heart rate and circulating levels of norepinephrine and plasma renin activity (37). The present data showed that levcromakalim increased skin blood flow in humans and further support the previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Pinacidil belongs to a first generation of K ATP channel opener. It is registered as an antihypertensive drug in Belgium (Therapress ) and Danmark (Pindac ) and the antihypertensive potency of the drug has been shown in several clinical studies [3,16,17,18,19,20,21,22].…”
Section: Discussionmentioning
confidence: 99%